Managing production engineering change and stability - Winch, Graham (Oxford Clarendon, 2011)
Explores how 15 of Britain's engineering firms are facing up to the challenges of the 1990s - global competition; lean production; and giving the customer value for money - and draws some lessons for the future.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Production management